Grammar - Swan, Michael (Oxford University Press, 2005)
Leading grammar expert Michael Swan answers questions such as, What is grammar for? How does it relate to vocabulary? How does it change? How does it differ across other languages? This accessible and readable introduction uses very little technical jargon in offering a fresh, original look at the subject.